2017
DOI: 10.2807/1560-7917.es.2017.22.13.30498
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for MERS coronavirus infection in dromedary camels in Burkina Faso, Ethiopia, and Morocco, 2015

Abstract: Understanding Middle East respiratory syndrome coronavirus (MERS-CoV) transmission in dromedary camels is important, as they consitute a source of zoonotic infection to humans. To identify risk factors for MERS-CoV infection in camels bred in diverse conditions in Burkina Faso, Ethiopia and Morocco, blood samples and nasal swabs were sampled in February–March 2015. A relatively high MERS-CoV RNA rate was detected in Ethiopia (up to 15.7%; 95% confidence interval (CI): 8.2–28.0), followed by Burkina Faso (up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 35 publications
8
86
3
Order By: Relevance
“…Large and medium herd-size was a significant risk factor for seropositivity across Burkina Faso, Morocco and Ethiopia, as well as nomadic and sedentary husbandry systems as opposed to a mixed lifestyle (Miguel et al, 2017). Conversely, in Kenya there was a non-statistically significant trend for smaller herds to have higher seroprevalence (Deem et al, 2015).…”
Section: Sample Population Characteristicsmentioning
confidence: 84%
See 3 more Smart Citations
“…Large and medium herd-size was a significant risk factor for seropositivity across Burkina Faso, Morocco and Ethiopia, as well as nomadic and sedentary husbandry systems as opposed to a mixed lifestyle (Miguel et al, 2017). Conversely, in Kenya there was a non-statistically significant trend for smaller herds to have higher seroprevalence (Deem et al, 2015).…”
Section: Sample Population Characteristicsmentioning
confidence: 84%
“…A. Dighe, et al Epidemics 29 (2019) 100350 Increase with age p = 0.032 (Miguel et al, 2017) Egypt < 2yrs 52% (n = 81) ≥2yrs 87% (n = 950)…”
Section: Agementioning
confidence: 98%
See 2 more Smart Citations
“…The investigation of dromedary camel serum collections, some of which collected as early as 1983, demonstrated that the virus was already widespread (seropositivity rate > 80%) in the East African countries (Somalia, Sudan and Egypt). These countries export dromedary camels to Arabian countries, but also in Kenya, Nigeria, Tunisia, Ethiopia, Burkina Faso and Morocco [12][13][14]. Phylogenetic analysis revealed 5 distinct coronavirus lineages in dromedary camels, including one recombinant lineage that led to the MERS-CoV epidemic in humans [15].…”
Section: Natural Reservoir Of Mers-covmentioning
confidence: 99%